Behind that 'Made-in-China' label: a shortcut, short-change, save-face story - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
China’s reputation as the world’s factory is not always matched with an equally positive reputation for the quality of its produce. Yet, the world’s consumers cannot seem to wean themselves off the economic giant's low cost products – neither can businesses. But do Chinese manufacturers really deserve the bad rep? Paul Midler, a Chinese-speaking American, shared his personal take at SMU recently, on what drives Chinese producers to do what they do, and how, he thinks, things can take a turn for the better.